A human minisatellite hosts an alternative transcription start site for NPRL3 driving its expression in a repeat number‐dependent manner. Issue 4 (31st January 2020) - Bertuzzi, Maria; Tang, Dave; Calligaris, Raffaella; Vlachouli, Christina; Finaurini, Sara; Sanges, Remo; Goldwurm, Stefano; Catalan, Mauro; Antonutti, Lucia; Manganotti, Paolo; Pizzolato, Gilberto; Pezzoli, Gianni; et al.
Abstract: Minisatellites, also called variable number of tandem repeats (VNTRs), are a class of repetitive elements that may affect gene expression at multiple levels and have been correlated to disease. Their identification and role as expression quantitative trait loci (eQTL) have been limited by their absence in comparative genomic hybridization and single nucleotide polymorphisms arrays. By taking advantage of cap analysis of gene expression (CAGE), we describe a new example of a minisatellite hosting a transcription start site (TSS) which expression is dependent on the repeat number. It is located in the third intron of the gene nitrogen permease regulator like protein 3 ( NPRL3 ). NPRL3 is a component of the GAP activity toward rags 1 protein complex that inhibits mammalian target of rapamycin complex 1 (mTORC1) activity and it is found mutated in familial focal cortical dysplasia and familial focal epilepsy. CAGE tags represent an alternative TSS identifying TAGNPRL3 messenger RNAs (mRNAs). TAGNPRL3 is expressed in red blood cells both at mRNA and protein levels, it interacts with its protein partner NPRL2 and its overexpression inhibits cell proliferation. This study provides an example of a minisatellite that is both a TSS and an eQTL as well as identifies a new VNTR that may modify mTORC1 activity.